139k views
1 vote
Multiply the following polynomials: i) (3x-8)•(4x+7)= ii) (4x + 7)² = iii) (3x –8)•(3x+8)=

User Pitermarx
by
5.2k points

1 Answer

5 votes

Multiply the following polynomials;

(1)


\begin{gathered} (3x-8)*(4x+7) \\ =(3x*4x)+(3x*7)-(8*4x)-(8*7) \\ =12x^2+21x-32x-56 \\ =12x^2-11x-56 \end{gathered}

(2)


\begin{gathered} (4x+7)^2 \\ =(4x+7)(4x+7) \\ =(16x^2+28x+28x+49) \\ =16x^2+56x+49 \end{gathered}

(3)


\begin{gathered} (3x-8)(3x+8) \\ =9x^2+24x-24x-64 \\ =9x^2+0-64 \\ 9x^2-64 \end{gathered}

User Larusso
by
5.1k points